Confocal endomicroscopy for evaluation of pancreatic cystic lesions: a systematic review and international Delphi consensus report - Napoleon, Bertrand; Krishna, Somashekar G.; Marco, Bruno; Carr-Locke, David; Chang, Kenneth J.; Ginès, Àngels; Gress, Frank G.; Larghi, Alberto; Oppong, Kofi W.; Palazzo, Laurent; Kongkam, Pradermchai; Robles-Medranda, Carlos; Sejpal, Divyesh; Tan, Damien; Brugge, William R. (Endoscopy International Open, 2020)
Background and study aims The aim of thi systematic review and consensus report is to standardize the practice of endoscopic ultrasound (EUS-guided needle-based confocal laser endomicroscopy (nCLE) for pancreatic cystic lesion (PCL) evaluation. Methods We performed an international, systematic, evidence-based review of the applications, outcomes, procedural processes, indications, training, and credentialing of EUS-nCLE in management of PCLs. Based on available clinical evidence, preliminary nCLE consensus statements (nCLE-CS) were developed by an international panel of 15 experts in pancreatic diseases. These statements were then voted and edited by using a modified Delphi approach. An a priori threshold of 80 % agreement was used to establish consensus for each statement.Results Sixteen nCLE-CS were discussed. Thirteen (81 %) nCLE-CS reached consensus addressing indications (non-communication PCL meeting criteria for EUS-FNA or with prior non-diagnostic EUS-FNA), diagnostic outcomes (improved accuracy for mucinous PCLs and serous cystadenomas with substantial interobserver agreement of image patterns), low incidence of adverse events (fluorescein-associated and pancreatitis), procedural processes (nCLE duration, manipulation of needle with probe), and training (physician knowledge and competence).Conclusion Based on a high level of agreement pertaining to expert consensus statements, this report standardizes the practice of EUS-nCLE. EUS-nCLE should be systematically considered when EUS-FNA is indicated for PCL evaluation.